Application of a geostatistical algorithm for correcting well logging data when modelling complex hydrocarbon deposits at the stage of additional field exploration - V. L. Shuster; O. V. Tjukavkina; I. S. Permyakova; I. L. Kapitonova (Известия высших учебных заведений: Геология и разведка)
Background. Additional exploration of oil and gas reserves requires the application of information technologies for modelling all technological processes and interpreting the results of geophysical well logging. Reliable models of the object under exploration and the use of best practices in the field of information systems reduce investment risks associated with planning exploration works, at the same time as optimizing the planning and design of the entire process of field development.Aim. Optimization of the selection process of multivolume, multiparameter logging data when modelling a complex oil reservoir at the stage of additional field exploration, grouping well data by quality, completeness and uniformity of their distribution over the study area, as well as identifying inaccuracies (errors) in the field data (registration of signals in probes, errors in measurements of directional survey, borehole picks, etc.).Materials and methods. Examples of well logging interpretation for a complex reservoir are given, along with its distribution options for a constructed lithology cube (2D, 3D) based on the data obtained during drilling from one pilot borehole – a horizontal well, a sidetrack and a directional well. It was established that the data obtained when distributing the reservoir and modelling the lithology cube of a complex development target can be significantly different for wells located close to each other. The results obtained when constructing 2D and 3D models by different specialists revealed discrepancies in the interpretation and cross-well correlation of well sections.Results. Local zones with a sharp change in the structure were established, in particular, the concentration of extrema around some wells. The presence of such anomalies points to the presence of wells, for which the values of stratigraphic depth marks for wells located close to each other are quite different. A geostatistical algorithm was applied to correct the well data using the “sliding window” method, which became a solution for the most accurate determination of the depths of the object under exploration.Conclusions. The possibility of using a geostatistical algorithm for correcting well data based on multiparameter geophysical data was assessed; the current state of modelling the processes of exploration and development of oil fields with a complex geological structure was analysed.